Del carrusel al juego de las sillas: ilegalidad y violencia en los procesos electorales locales; From Carousel to Musical Chairs Illegality and Violence in Local Electoral Processes - Rodriguez Dominguez, Emanuel (Universidad Autónoma Metropolitana, 2019)
The increase in environments of unrest and political violence in the electoral process of the last decade is analyzed here. Murder and aggression toward candi- dates in popular vote appointments data is recovered; furthermore, an ethnographic reconstruction of the repertoire of violent activity as more and more frequent in the local scope is presented. The correlation between alternation processes and electoral competitiveness and the emergence of party tactics that use violence to uphold power in the demarcations of Mexico City is investigated, and how these arrays are employed by parties to assert or reach power in local enclaves is described. From a perspective that highlights the social function of fear, it is concluded that the repertoires of violence have a considerable impact in the practices and collective worldview of the inhabitants of the city.; Se analiza el aumento de los climas de tensión y violencia política en los procesos electorales de la última década. Se recuperan datos de asesinatos y agresiones a candidatos a puestos de elección popular; a la par, se presenta una reconstrucción etnográfica de repertorios de acción violenta cada vez más frecuentes en el ámbito local. Se investiga la correlación entre procesos de alternancia y competitividad electoral y el surgimiento de tácticas partidarias que usan la violencia para mantener el poder en las demarcaciones de la Ciudad de México, y se describe cómo dichos repertorios son empleados por los partidos para mantener o alcanzar el poder en los enclaves locales. Desde una perspectiva que pone el acento en la función social del miedo, se concluye que los repertorios de violencia impactan considerablemente las prácticas e imaginarios político-electorales de los habitantes de la ciudad.